PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN ( STUDI KASUS PADA KARYAWAN PT. DUTA LOGISTIK ASIA) - HARYANTO .; WASIMAN . (JURNAL ILMIAH SIMANTEK, 2020)
This study aims to analyze the Effect of Compensation and Job Satisfaction on Employee Performance of PT. Duta Logistik Asia. The entire population in this were employees at the company, amounting to 112 people, and at the same time served as sample of respondents.Variables in this study consisted of compensation, Job satisfaction as independent variables employee performance as the dependent variable. Multiple linear regression was used in this study. The results of the research that have been carried out give a conclusion: that compensation has a positive and significant effect on employee performance, this is evidenced by the probability value 0.017 < 0.05. While job satisfaction has a positive and significant effect on employee performance at the level of significant 0.000 < 0.05. So first and second hypotheses in the study declared, accepted. Another result is that compensation and job satisfaction, simultaneously have a positive and significant effect on employee performance with a significance 0.000 < 0.05, thus the third hypothesis is accepted.Value of R2 in this is 68.2%, this means that the change in employee performance variables is influenced by compensation and satisfaction variables by 68.2% the rest is influenced by other variables that’s not included in this study.